Implementing Flipped Classroom Model Integrated with Interactive Multimedia To Enhance Students’ Writing Ability at English Tadris Program of UIN Datokarama Palu - Rasmi; Muhammad Ihsan (Eduvelop: Journal of English Education and Development, 2023)
This experimental research implemented Flipped Classroom Model (FCM) in teaching writing with interactive multimedia, aiming at exploring whether FCM can enhance the students’ writing ability. The research was conducted at the second semester students of English Department Students Islamic State University of Datokarama Palu. This research assigned two groups namely experimental and control group. The sample was selected using taken by applying purposive sampling. A group of 18 students were taught by implementing flipped classroom model while in other group students were given conventional way. The Instrument of this research was writing decriptive test. The data obtained through the test were analyzed by using statistical analysis and SPSS 20. Based on the result of research the mean score of post-test of experimental group (84.11) was higher than control group (75.52). The result of the t-test value (7.175) was higher than t-table value (2.000). In other words, H0 was rejected and H1 was accepted. This means that implementing implementing flipped classroom model with interactive multimedia enhance the students’ writing ability significantly of the second grade students atof English Department Students Islamic State University of Datokarama Palu